ANALISIS KUALITAS BUTIR SOAL UJIAN AKHIR SEMESTER GANJIL MATA PELAJARAN INFORMATIKA KELAS X DI SMKN 8 JEMBER TAHUN AJARAN 2022/2023 - Ramadhani, Dhea Putri; Priyanto (Journal of Information Technology and Education (JITED), 2024)
The purpose of this research is to find out how the quality of item final examination semester test on the informatics subjects of the Class X at SMKN 8 Jember in the 2022/2023 academic year by reviewing the aspects of validity, reliability, level of difficulty, power differentiator, and the effectiveness of the detractors. The type of research approach used in this research is a quantitative approach, with a descriptive research design. The population in this study was all Class X students who took informatics lessons at SMKN 8 Jember in the 2022/2023 school year with a total of 560 people. So the research sample consists of the entire existing population. Interviews and documentation studies are some of the techniques used in collecting data. The data taken in the form of final semester exam test documents consisting of student answer sheets, exam questions, and the answer keys. The data was analyzed by reviewing aspects of validity, reliability, power differentiator, level of difficulty, and the effectiveness of the detractors using the help of Anates Version 4.09 software which can be used to determine the quality of each item. The results of this study indicate that: (1) 3 items (12%) in the sufficient category, (2) 11 items (44%) in the good category, these items must be revised first so that they can be reused, (3) 11 items (44%) in the very good category, the items in this category do not need to be revised.